2013
DOI: 10.1074/jbc.m113.467506
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of E2F7 Transcription Factor with E2F1 and C-terminal-binding Protein (CtBP) Provides a Mechanism for E2F7-dependent Transcription Repression

Abstract: Background: E2F7 is a transcription factor that controls cell cycle by repressing the expression of G 1 /S genes in late S phase. Results: E2F7 forms a heterodimer with E2F1, and it recruits the co-repressor CtBP to repress G 1 /S transcription. Conclusion: E2F7 represses gene transcription by interacting with E2F1 and co-repressor CtBP. Significance: These findings suggest a mechanism for the repression of transcription by E2F7.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 41 publications
1
30
0
Order By: Relevance
“…Although we identified E2F7 in the CtBP2-protein complex, we showed that it interacts with CtBP1 as well. During the preparation of this manuscript another report identified CtBP1 and CtBP2 as E2F7-interacting proteins [23]. Our results indicate that E2F7 interacts with the hydrophobic cleft region of CtBP since a mutation of a critical residue A58 of CtBP2 (corresponding to A52 of CtBP1) within the hydrophobic cleft region abolished E2F7 interaction.…”
Section: Discussionmentioning
confidence: 61%
“…Although we identified E2F7 in the CtBP2-protein complex, we showed that it interacts with CtBP1 as well. During the preparation of this manuscript another report identified CtBP1 and CtBP2 as E2F7-interacting proteins [23]. Our results indicate that E2F7 interacts with the hydrophobic cleft region of CtBP since a mutation of a critical residue A58 of CtBP2 (corresponding to A52 of CtBP1) within the hydrophobic cleft region abolished E2F7 interaction.…”
Section: Discussionmentioning
confidence: 61%
“…Both Foxm1 and E2F1 are transcriptional activators involved in cell proliferation (Stender et al 2007; Real et al 2011). E2F7 represses the activity of E2F1 by binding to E2F1-responsive genes (De Bruin et al 2003; Liu et al 2013). However, at 24 h, E2F7 is only enriched in the set of upregulated genes.…”
Section: Resultsmentioning
confidence: 99%
“…Both Foxm1 and E2F1 are transcriptional activators involved in cell proliferation (Stender, Frasor et al 2007, Real, Meo-Evoli et al 2011. E2F7 on the other hand represses the activity of E2F1 by binding to E2F1-responsive genes (De Bruin, Maiti et al 2003, Liu, Shats et al 2013). However at 24h, E2F7 is only enriched in the set of up-regulated genes providing further evidence to the generic cell cycle signature at later times.…”
Section: Cell Cycle Alterations At 24hmentioning
confidence: 99%